Blocking hepatic metastases of colon cancer cells using an shRNA against Rac1 delivered by activatable cell-penetrating peptide - Bao, Ying (Oncotarget, 2016)
Hepatic metastasis is one of the critical progressions of colon cancer. Blocking this process is key to prolonging survival time in cancer patients. Studies on activatable cell-penetrating peptides (dtACPPs) have demonstrated their potential as gene carriers. It showed high tumor cell-targeting specificity and transfection efficiency and low cytotoxicity in the in vitro settings of drug delivery. However, using this system to silence target genes to inhibit metastasis in colorectal cancer cells has not been widely reported and requires further investigation. In this study, we observed that expression of Rac1, a key molecule for cytoskeletal reorganization, was higher in hepatic metastatic tumor tissue compared with prime colon cancer tissue and that patients with high Rac1-expressing colon cancer showed shorter survival time. Base on these findings, we created dtACPP-PEG-DGL (dtACPPD)/shRac1 nanoparticles and demonstrated that they downregulated Rac1 expression in colon cancer cells. Moreover, we observed inhibitory effects on migration, invasion and adhesion in HCT116 colorectal cancer cells in vitro, and our results showed that Rac1 regulated colon cancer cell matrix adhesion through the regulation of cytofilament dynamics. Moreover, mechanically, repression of Rac1 inhibiting cells migration and invasion by enhancing cell to cell adhesion and reducing cell to extracellular matrix adhesion. Furthermore, when atCDPPD/shRac1 nanoparticles were administered intravenously to a HCT116 xenograft model, significant tumor metastasis to the liver was inhibited. Our results suggest that atCDPP/shRac1 nanoparticles may enable the blockade of hepatic metastasis in colon cancer.